Perception of Nigeria wildlife conservation laws among officials of Okomu and Old Oyo National Parks, Nigeria (2019)
This study assessed the perception of Nigeria wildlife conservation laws by officials of Okomu and Old Oyo National Parks. Data was collected from 180 respondents using semi-structured questionnaire. The results showed that the officials perceive that Nigeria wildlife laws are essential for conservation of wildlife and that the laws can stop wildlife exploitation. They however perceived that the fines, penalties and punishment as stated in the law are inadequate to stop illegal hunting with indications that the amount charged for killing wild animals is not commensurate to the offence. Furthermore, the park officials indicated that Nigeria wildlife laws are obsolete and in need of a review. No significant difference exists in the perception of the laws among the parks. It is therefore recommended that; the Nigerian wildlife laws having been considered obsolete by the custodians of the national parks should be urgently reviewed for effective management of wildlife in Nigeria.